RISK AS AN ANTECEDENT VARIABLES OF BANK SOUNDNESS WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE ON PRIVATE COMMERCIAL BANKS LISTED IN THE INDONESIA STOCK EXCHANGE - Chaniago, herizon (Archives of Business Research, 2018)
The sound banking industry is needed every country including Indonesia. Private commercial banks listed on the Indonesia Stock Exchange still have soundness problems, because in the last five years of 2012 until 2016 their soundness tends to decline as evidenced by the declining trend of soundness scores. The critical objective of this research is to investigate and know the antecedent variables of bank soundness and the ability of the GCG variable in influencing from risk to bank soundness. The population of this research is private commercial banks listed in Indonesia Stock Exchange and by using purposive sampling technique selected 22 banks as sample research. The period of this study is from 2012 to 2016. The variables in this research include credit risk, market risk liquidity risk, operational risk and GCG as the independent variable and bank soundness as the dependent variable. Risk indicator data are collecting by downloading the financial statements for the last five years from the sites Financial Services Authority (OJK). Data about GCG was taken from annual bank report and bank soundness data taken from Infobank magazine. In conducting the research hypothesis proof, used WarpPLS software. The results obtained from this research are credit risk and operational risk performance into an antecedent variable of bank soundness because it has a significant effect on the bank soundness, while a market risk, liquidity risk, and GCG do not become antecedent variable bank soundness due to the insignificant effect on the bank soundness. GCG moderates the impact of credit risk, market risk, liquidity risk and operational risk to bank soundness.